2004
DOI: 10.1007/s00011-004-1254-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nitric oxide and proteoglycan synthesis due to cyclic tensile strain loaded on chondrocytes attached to fibronectin

Abstract: Cyclic tensile strain loaded on the chondrocytes enhanced NO synthesis and this enhanced NO inhibited PG synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…In particular, Matsukawa et al (2004) observed that on fibronectin coated plates, proteoglycans increased. Whereas on collagen I coated culture plates, proteoglycans were decreased [ 31 , 47 ]. On pronectin coated plates, no changes between unloaded cells and cells under CTS were observed [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Matsukawa et al (2004) observed that on fibronectin coated plates, proteoglycans increased. Whereas on collagen I coated culture plates, proteoglycans were decreased [ 31 , 47 ]. On pronectin coated plates, no changes between unloaded cells and cells under CTS were observed [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study found an increase in iNOS and NO at 0.05 Hz [ 76 ]. However, higher frequencies (0.17 and 0.5 Hz) up-regulated especially COX-2 and with increasing loading duration also iNOS, NO and PGE 2 [ 26 , 28 , 36 , 37 , 47 ]. Matsukawa et al (2004) reported that CTS stimulated iNOS mRNA only on fibronectin coated culture plates, but not on collagen coating.…”
Section: Resultsmentioning
confidence: 99%
“…This study evaluated one level of chronic load alteration (100%BW) at two select time points (6 and 20 weeks) and unquestionably demonstrates the induction of joint degeneration by altered load. In vitro studies have shown that abnormal mechanical forces can stimulate articular chondrocytes to produce pro-inflammatory mediators [3336], that promote matrix degradation through a variety of metabolic pathways. The use of the VLD-model will allow elucidation of the mechanisms of in vivo chronic load-induced joint degeneration in future studies which evaluate early changes following shorter durations of altered loading.…”
Section: Discussionmentioning
confidence: 99%
“…Production of proteoglycans containing acidic glycosaminoglycans as well as production of hyaluronic acid by cells is upregulated by cyclic shearing, tensile and compression strain (Dowthwaite et al, 1999;Lee et al, 2000;Matsukawa et al, 2004;Grad et al, 2005). These substances entrap large quantities of water, which is removed from the proteoglycan aggregates when pressure is applied.…”
Section: Discussionmentioning
confidence: 99%